Compressive Strength of MICP-Treated Silica Sand with Different Particle Morphologies and Gradings. Issue 2 (1st February 2022) - Song, Chenpeng; Wang, Chaoyi; Elsworth, Derek; Zhi, Sheng
Abstract: Microbially-induced calcium carbonate precipitation (MICP) can enhance the stiffness and bulk strength of sand aggregates via calcium carbonate cementation. This study explores the mechanical strength of silica sand aggregates with different particle morphologies and sizes following MICP treatment. Specifically, unconfined uniaxial compressive strength (UCS) of MICP-treated spherical, near-spherical, and angular aggregates are measured for four separate size fractions (18–25, 25–40, 40–60, and 60–80 mesh). Scanning electron microscope (SEM) imaging is performed on post-treatment samples to investigate the difference in cementation morphology and failure mechanisms. The experimental results indicate: (1) given identical cycles of MICP treatment, the UCS of treated spherical and near-spherical sands peaks at 25–40 mesh particle size, while the treated angular sands show increasing UCS with decreasing particle size; (2) spherical sands have the highest calcium carbonate (CaCO3 ) content given identical MICP cycles; and (3) higher post-treatment CaCO3 content does not correlate to higher UCS—implying that the distribution and morphology of CaCO3 precipitation exert crucial control. SEM analysis shows that CaCO3 fully encapsulates spherical sand particles uniformly, forming point contact bonds. In contrast, CaCO3 precipitations show a patchy distribution on near-spherical and angular sand grain surfaces. Unlike treated spherical sands, treated near-spherical sands feature a mixture of point and planar contact bonds while treated angular sands feature predominantly planar contact bonds. Planar contact bonds provide a larger effective cementation area between sand particles and thus result in higher bonding strength. The particle morphology and resultant inter-particle bonding morphology help reconcile higher ensemble UCS with lower CaCO3 content of treated angular sands.